Analysis of Game-Based Learning Models in Mathematics Education at SDN Segara Makmur 01 - Suprihatin, Suprihatin; Mukhlis, Mukhlis; Syukur, Abdul; Komariah, Euis; Arizona, Herbeta; Suntari, Susi; Musliman, Acep; Munali, Munali (ATTA`DIB, 2025)
This study aims to analyze the application of the game-based learning model in mathematics lessons in grade V at SDN Segara Makmur 01, Bekasi Regency. This study uses a qualitative approach and data collection through interviews, observations, and documentation. The results of the study show that the implementation of the game-based learning (GBL) model was carried out in several stages, namely the preparation stage for game-based mathematics learning, the implementation stage, and the evaluation stage. This model has been proven to be effective in increasing learning creativity. The increase in student creativity can be seen in their curiosity, fluency, flexibility, and originality.